PENGEMBANGAN E-LKPD BERBANTUAN LIVEWORKSHEETS MATERI ORGAN GERAK MANUSIA KELAS V SDN 02 PODO - Lana Fauziyah; Petra Kristi Mulyani (Prima Magistra: Jurnal Ilmiah Kependidikan, 2023)
This research is motivated by the lack of availability of teaching materials used during the implementation of learning. Teachers have never used interactive media such as electronic worksheet media. This study aims to produce a product in the form of an e-LKPD assisted by Liveworksheets on material for human movement organs for grade V SD. Research and Development (R&D) research with the ADDIE development model is the type of research used in the development of this e-LKPD. The research was conducted at SDN 02 Podo, Pekalongan Regency in the even semester of the 2022/2023 academic year. The instrument used was a validation sheet given to 2 validators (media expert validator and material expert validator), user response sheets to a grade V teacher and 27 students. The results of the study obtained an average percentage score of the validator's assessment of media experts and material experts of 90.9% and 100% in the very feasible category. the results of the responses of teachers and students each obtained a score of 100% and 93.9% in the very good category. From the results of the study it can be concluded that e-LKPD assisted by Liveworksheets on the material of human movement organs is suitable for use as a learning media.